Pengembangan blog sebagai media dalam pembelajaran berbasis proyek - Eni Latifah; Heru Kuswanto (Jurnal Pendidikan Matematika dan Sains, 2018)
Penelitian ini bertujuan untuk: mengetahui peningkatan  kemampuan pemecahan masalah dan keterampilan kerja sama peserta didik kelas. Metode yang digunakan dalam penelitian ini adalah Research and Development (RD) yang menggunakan model 4-D (four D model). Populasi penelitian ini adalah peserta didik kelas X MAN Yogyakarta III pada semester kedua tahun ajaran 2014/2015. Teknik pengumpulan data yang digunakan adalah teknik observasi dan tes. Teknik observasi digunakan untuk mengetahui keterampilan kerja sama peserta didik. Aspek keterampilan kerja sama yang diteliti adalah bekerja produktif, tanggung jawab dan fleksibilitas. Tes digunakan untuk mengetahui kemampuan pemecahan masalah peserta didik pada pokok bahasan Alat-Alat Optik sebelum dan sesudah perlakuan. Teknik analisis data yang digunakan adalah teknik peningkatan gain, kemudian dilanjutkan dengan uji multivariate ( MANOVA).  Hasil penelitian ini menunjukan bahwa : Blog sebagai media dalam pembelajaran fisika dapat meningkatkan kemampuan pemecahan masalah dan keterampilan kerja sama peserta didik.The Development of Blog as Media in Project-Based Learning AbstractThis study aims to:  know the increase of student’s problem solving skills and teamwork skills. The method used in this research was the Research and Development (R D) using  4-D models. The population of this experiment were students of class X MAN Yogyakarta III in the second half of the school year 2014/2015. The data were collected through observation and test. The Observation technique was used to determine the student cooperation. Aspects of cooperation skills studied were working productively, responsibility and flexibility. The test was used to determine the problem solving ability of students in the subject Optical Devices before and after treatment. Data analysis technique used was the technique of the increase in gain scores, followed by multivariate test (MANOVA). These results indicate that: Blogs as a media-based learning PjBL can improve problem solving and teamwork skills.Keywords: development, learning devices, PjBL, teamwork skills, problem solving abilityAbstract This study aims to:  know the increase of student’s problem solving skills and teamwork skills. The method used in this research was the Research and Development (R D) using  4-D models. The population of this experiment were students of class X MAN Yogyakarta III in the second half of the school year 2014/2015. The data were collected through observation and test. The Observation technique was used to determine the student cooperation. Aspects of cooperation skills studied were working productively, responsibility and flexibility. The test was used to determine the problem solving ability of students in the subject Optical Devices before and after treatment. Data analysis technique used was the technique of the increase in gain scores, followed by multivariate test (MANOVA). These results indicate that: Blogs as a media-based learning PjBL can improve problem solving and teamwork skills.